'Should I stay or should I go?' : the additive double qualification pathway in Germany - Edeling, Sabrina [Verfasser]; Pilz, Matthias [Verfasser] (My University, 2017)
"A striking number of young people in Germany with the Abitur - the qualification required for entry to higher education - do not, in fact, go on to university immediately after leaving school but opt first to do an apprenticeship. This phenomenon, where general and vocational curricula are taught independently and separately, is known as the 'additive double qualification pathway' and represents an extreme type of hybrid qualification. This paper considers a range of individual influences in an attempt to obtain a holistic view of the possible motives of those who opt for this pathway. The study focuses on apprentices with the Abitur who were surveyed as they were about to complete their vocational training and were on the point of moving on to a university or university of applied sciences (Fachhochschule). The research investigates four very different training occupations with relatively high proportions of Abitur holders: industrial clerk; bank clerk; optician; and motor vehicle mechatronics technician. It is a large-scale quantitative research study (n = 1234). The range of possible motives is hypothesised, systematically operationalised and finally tested empirically." (authors' abstract; BIBB-Doku)
Keywords: P 2.1.5 Fachhochschul- und Hochschulreife; S 1.3 Berufliche Erstausbildung; S 1.4 Hochschulbildung; Abiturient; Berufsausbildung; Studium; Doppelqualifikation; Einflussfaktor